Revision of the African genus Uvariastrum (Annonaceae) - (:unkn) unknown (My University, 2014)
The genus Uvariastrum (Annonaceae) is restricted to continental Africa and is characterized by sepals with folded margins, few carpels and numerous stamens. The genus is mainly found in the tropical lowland rain forests of Africa, with one species growing in a drier woodland habitat. The species name Uvariastrum pynaertii De Wild is reduced into synonymy with Uvariastrum zenkeri Engl. & Diels. Uvaraistrum neglectum Paiva and Uvariastrum modestum Dielsare transferred to the genus Uvaria leading to two new combinations: Uvaria modesta (Diels) Couvreur, comb. nov. and Uvaria paivana Couvreur, nom. nov. Five species are currently recognized in Uvariastrum. The present revision, the first of the genus for over 100 years, provides an overview of previously published information and discussions on morphology, taxonomy and palynology. Preliminary conservation status assessments are provided for each species, as well as diagnostic keys for fruiting and flowering material as well as detailed species descriptions. Furthermore, all species are illustrated by line drawings and all species are mapped.
Keywords: African Research